Successful treatment of ruptured multiple fusiform middle cerebral artery aneurysms with Silk Vista Baby flow diverter in a 10-month-old infant. Issue 8 (29th August 2022) - Barchetti, Giovanni; Di Clemente, Loris; Mazzetto, Mauro; Zanusso, Mariano; Ferrarese, Paola; Iannucci, Giuseppe
Abstract : We report the successful treatment of multiple ruptured fusiform middle cerebral artery (MCA) aneurysms in a 10-month-old girl. This previously healthy infant presented with subarachnoid hemorrhage and was found to have multiple irregular dilatations of the superior division branch of the right MCA. Cerebral angiography was performed and confirmed the presence of multiple fusiform aneurysms of the MCA. After discussion with the multidisciplinary team, it was decided to treat the aneurysms with a endovascular approach, using a flow diverter. Microsurgical clipping was deemed risky because of the high likelihood of parent artery occlusion, and expectant management was also considered inappropriate because of the risk of rebleeding. Dual antiplatelet therapy was started, and a flow diverter was successfully delivered in the superior division branch of the right MCA. The postoperative course was uneventful, MRI at 12 months did not show any sign of recurrence, and at 3 years of age the patient had a normal neurological examination.